A priori Estimate for the solution of Sylvester equation - Mansour, Abdelouahab; Bekkar, L. Hariz; Gaaya, H (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
For A, B and Y operators in B(H) it’s well known the importance of sylvester equation AX - XB= Y in control theory and its applications. In this paper -using integral calculus- we were able to give a priori estimate of the solution of famous sylvester equation when A and B are selfadjoint operators, some other results are also given.